The effects of exercise training on body composition in postmenopausal women: a systematic review and meta-analysis - Khalafi, Mousa; Habibi Maleki, Aref; Sakhaei, Mohammad Hossein; Rosenkranz, Sara K.; Pourvaghar, Mohammad Javad; Ehsanifar, Mahsa; Bayat, Hadis; Korivi, Mallikarjuna; Liu, Yubo (Frontiers in Endocrinology, 2023)
Abstract We conducted a systematic review and meta-analysis to investigate the effect of exercise training on body composition outcomes in postmenopausal women. PubMed, Web of Science, CINAHL, and Medline were searched to identify the randomized controlled trials which evaluated effect of exercise training versus control in postmenopausal women. Standardized mean differences (SMD), weighted mean differences (WMD) and 95% confidence intervals (95% CIs) were calculated using random effects model. One hundred and one studies involving 5,697 postmenopausal women were included in the meta-analysis. Results indicated that exercise training effectively increased muscle mass/volume, muscle and fiber cross-sectional area and fat-free mass, and decreased fat mass, body fat percentage, waist circumference and visceral fat. Furthermore, subgroup analyses results revealed that aerobic and combined training had greater beneficial effects on fat mass outcomes, whereas resistance and combined training had greater beneficial effects on muscle mass outcomes. Overall, our results revealed that exercise training is effective for improving body composition in postmenopausal women. To be specific, aerobic training is effective on fat loss, whereas resistance training is effective on muscle gain. However, combination of aerobic and resistance trainings may be considered a viable strategy to improve body composition in postmenopausal women.